2012
DOI: 10.1088/0967-3334/33/11/1855
|View full text |Cite
|
Sign up to set email alerts
|

Validation of seat-off and seat-on in repeated sit-to-stand movements using a single-body-fixed sensor

Abstract: The identification of chair rise phases is a prerequisite for quantifying sitto-stand movements. The aim of this study is to validate seat-off and seaton detection using a single-body-fixed sensor against detection based on chair switches. A single sensor system with three accelerometers and three gyroscopes was fixed around the waist. Synchronized on-off switches were placed under the chair. Thirteen older adults were recruited from a residential care home and fifteen young adults were recruited among college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Other studies define consecutive sit-stand-sit cycles by a double flexion and extension movement [26,39,40]. Our research showed that this specific movement does not always occur, the X-orientation range we found during the impulse phase revealed that healthy subjects do not perform double flexion and extension.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Other studies define consecutive sit-stand-sit cycles by a double flexion and extension movement [26,39,40]. Our research showed that this specific movement does not always occur, the X-orientation range we found during the impulse phase revealed that healthy subjects do not perform double flexion and extension.…”
Section: Discussionsupporting
confidence: 48%
“…In the literature, only Van Lummel et al, [36] differentiate between correct SitTS movements and failed attempts. They employed the velocity information instead of the position, but they did not provide any further information about their methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Reliability of instrumented STS has been assessed against conventional movement analysis systems [103,104], whereas its sensitivity has been proved by comparing young and older adults [105,106]. For example, Regterschot and colleagues reported ICC≥0.90 and standard error of the measurement ≤9.9% [105].…”
Section: Instrumented Clinical Tests: Methodological Approachmentioning
confidence: 99%
“…A single IS, worn on the lower back, has successfully been used for analyzing sub-phases and trunk kinematics during chair rise (Giansanti and Maccioni, 2006;Millor et al, 2013;Schwenk et al, 2012;Van Lummel et al, 2012;Van Lummel et al, 2013;Weiss et al, 2011Weiss et al, , 2010 and have been validated against other instrumentation for the sit-to-stand task (Boonstra et al, 2006;Janssen et al, 2008;Zijlstra et al, 2012). But Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jbiomech www.JBiomech.com the validity of using an IS during the biomechanically challenging sit-to-walk (STW) task, which is common in daily life, has not yet been investigated (Kouta and Shinkoda, 2008).…”
Section: Introductionmentioning
confidence: 99%